A History of Changes that Enhanced The Role of Accounting: A Discussion of The Reforms in The UK National Health Service - Heru Fahlevi (Jurnal Akuntansi dan Bisnis, 2010)
This paper presents some aspects on the introduction of more commercial-like reforms in the UK National Health Service (NHS). It used adjusted Lüder’s Contingency Model modified by Pettersen (2004) as an alternative framework to explain how NHS reforms generate the innovation of accounting role in hospitals. The NHS reforms exercised by the Conservative and the New Labour have both similarities and differences in the rationale and the consequences. The applications of adjusted Lüder’s Contingency Model have assisted in outlining the similarities and differences between market reform and third way reform. The most striking similarity is both reforms were driven by the government political decision and the process of reforms implementation has been top-down organised. Moreover, it may be said that payment system has become a main tool to control the process of reforms and the hospital performance. But there are different as to use competition in price and competition in performance. However, the contingency model appears to present a limited explanation about how accounting role innovation process travelled between both reforms. Furthermore, this study is a desk research. Any generalisations of the conclusions from this study should be undertaken with care.